LAMP Detection of Virus-Derived DNA of Zika Virus in Vector Mosquito - Aonuma, Hiroka; Iizuka, Itoe; Li, Jian-Chiuan; Ote, Manabu; Tajima, Shigeru; Saijo, Masayuki; Chen, Chun-Hong; Kanuka, Hirotaka (Frontiers in Tropical Diseases, 2022)
Detection of infectious viruses in mosquitoes is one of the prerequisite measures to monitor the prevalence of vector-borne viral diseases. Determining which mosquitoes are currently infected with arboviruses such as Zika, dengue, and chikungunya virus is not yet practical in endemic areas due to multiple causes including the difficulty of dealing with the virus’ unstable RNA. In this study, instead of handling viral RNA, virus-derived DNA (vDNA) was introduced as a target template for nucleic acid amplification. In combination with loop-mediated isothermal amplification (LAMP), we examined a LAMP-based vDNA detection assay (vDNA-LAMP) targeting Zika virus (ZIKV). The vDNA-LAMP reaction amplifying part of the NS3 region of ZIKV successfully detected its vDNA from crude DNA purified from artificially infected cultured cells and Aedes mosquitoes. This rapid, simple, and versatile method may provide a promising field-surveillance method for arbovirus circulation via vector mosquitoes.